Discovery and optimization of a potent and selective indazolamine series of IRAK4 inhibitors. (1st January 2021) - Zhai, Wenqiang; Lu, Yongping; Zhu, Yabo; Zhou, Mengguang; Ye, Cheng; Shi, Zheng-Zheng; Qian, Wenjian; Hu, Taishan; Chen, Lei
Graphical abstract: Abstract: IRAK4 is a key mediator of innate immunity. There is a high interest in identifying novel IRAK4 inhibitors for the treatment of inflammatory autoimmune diseases. We describe here a highly potent and selective IRAK4 inhibitor (HS271) that exhibited superior enzymatic and cellular activities, as well as excellent pharmacokinetic properties. HS271 displayed robust in vivo anti-inflammatory efficacy as evaluated in rat models of LPS induced TNFα production and collagen-induced arthritis.